Incidence and epidemiological profile of Zika cases in two cities in different regions of the state of Pernambuco (Research, Society and Development, 2022)
The Zika virus is an arboviruses, transmitted by the Aedes aegypti mosquito, known by the acronym ZIKV, - a relative of the causes of other diseases, such as dengue, yellow fever and West Nile fever. This article aims to describe the epidemiological profile and incidence of Zika cases in the cities of Ipojuca and Petrolina in the state of Pernambuco. To this end, data surveys were used on the two cities from the Health Department of the State of Pernambuco (SESPE) and the Department of Informatics of the Unified Health System (DataSUS) from January to December 2019. The incidence, in synthesis, it is verified as the sum of variable factors, such as: sex, age, housing, education, race and financial condition, of the cities studied.